A Novel Immunophilin Ligand: Distinct Branching Effects on Dopaminergic Neurons in Culture and Neurotrophic Actions after Oral Administration in an Animal Model of Parkinson's Disease - L.C. Costantini; P. Chaturvedi; D.M. Armistead; P.G. McCaffrey; T.W. Deacon; O. Isacson (Neurobiology of Disease, 1998)
Protection or regeneration of the dopaminergic (DA) system would be of significant therapeutic value for Parkinson's disease. Immunophilin ligands, such as FK506, can produce neurotrophic effectsin vitroandin vivo,but their immunosuppressive effects make them unsuitable for neurological application. This study demonstrates that a novel, nonimmunosuppressive immunophilin ligand (V-10,367) increased the number of neurites extended by tyrosine hydroxylase positive (TH+) DA neurons in embryonic day 14 primary DA neuronal cultures. In contrast, the immunosuppressive immunophilin ligand FK506 increased the length of TH+ neurites. After oral administration in MPTP-treated mice, V-10,367 completely protected against MPTP-induced loss of striatal TH+ axonal density, while FK506 did not. These experiments demonstrate that nonimmunosuppressive immunophilin ligands specifically increase neurite branching in primary DA neuronal cultures and possess neurotrophic actionsin vivowith potential application to neurodegenerative disease.